New tri- and di-alkylstannyl 2-(1H-indol-3-yl)ethanoates: synthesis, characterization and biological screenings. Issue 6 (18th March 2020) - Shaheen, Farzana; Sirajuddin, Muhammad; Ali, Saqib; Shah, Naseer Ali; Kanwal, Balquees; Tahir, Muhammad Nawaz
Abstract: A series of triorganotin(IV) compounds Me3 SnL (1 ), Bu3 SnL (2 ), Ph3 SnL (3 ) and di-organotin(IV) complexes Me2 SnL2 (4 ), Bu2 SnL2 (5 ) and Ph2 SnL2 (6 ), where Me = methyl, Bu = butyl, Ph = phenyl and L = 2-(1H-indole-3-yl)acetate) have been synthesized and characterized by FT-IR and multinuclear NMR ( 1 H-, 13 C- and 119 Sn-NMR) spectroscopy. Tri- and diorganotin(IV) derivatives exhibited five- and six-coordinate geometries, respectively, in solid state as evident from the Δν value. Five-coordinate trigonal bipyramidal and six-coordinate octahedral geometry was assigned to 1 and 4 in solution state based on NMR data as evident from 2 J ( 119 Sn, 1 H) and 1 J ( 119 Sn- 13 C) coupling constant values, which was further attested by 119 Sn NMR. Single crystal XRD analysis on 1 revealed that it exhibited polymeric crystal structure with distorted trigonal bipyramidal geometry around the tin center with two unequal Sn–O bonds. The screening of the synthesized compounds for cytotoxicity showed good activity in comparison to cis- platin. They have also displayed moderate to good antimicrobial activities. Graphical Abstract: